Παραγωγή βιοντίζελ από xρησιμοποιημένα έλαια - Χριστοδούλου, Ελένη (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The diesel engines were constructed by Dr. Rudolph in 1900 in which he used first vegetable oils, but later used diesel for economic reasons. With the oil crisis, the reduction of non-conventional fuels and reason the environmental problems caused by burning these, carried out research on alternative fuels mentioned primarily as biofuels. The use of biofuels offers advantages as reducing emissions in the atmosphere that cause many environmental problems, rural development and a country disengagement from fuel imports after it is domestic product. Vegetable oils are considered biofuels for diesel engines, although they have some advantages their use causes many problems in machinery, because of their characteristics that differ greatly from those of diesel fuel. Biodiesel is commonly produced from vegetable oils and is a clean biofuel produced from renewable energy sources, contribute in decreasing exhaust emissions compared to petroleum diesel, which has similar physicochemical properties when used either alone, or blended with petroleum diesel, reason of oxygen containing. In the present work is envisaged production of biodiesel from used cooking oil, which method is most suitable transesterification and comparing emissions of biodiesel in the atmosphere than burning diesel through laboratory studies. Also study the production of biodiesel from several types of waste cooking oil in frequency different use for cooking. The results showed that the best method was to base-catalyzed transesterification and biodiesel either as such or in mixtures with diesel engines diesel dire lower emissions CO, CO2, SO2, NOx and particulate matter (PM), but higher emissions of NO2 . In laboratory application, results showed with increasing frequency of use of the oils for frying 2-7 times biodiesel decreases from 90% to 85%, and that excessive use over 7 times using, not produced biodiesel obtained glycerol only.
Keywords: Diesel Engine; Μηχανή Ντίζελ